The transversal strength of acrylic resin plate after being immersed soaking in noni fruit (Morinda citrifolia Linn.) juice - Sri Redjeki Indiani (Dental Journal (Majalah Kedokteran Gigi), 2008)
The disadvantages of acrylic resin plate are liquid absorption and porosity, allowing microorganisms to grow and multiply resulting in inflammation in the oral cavity. The juice of the noni fruit (Morinda citrifolia Linn.) contains active flavonoid and atsiri oil. Flavonoid is a phenol substance that degrades acrylic resin plate in prolonged contact. The purpose of this study was to examine the transversal strength of acrylic resin plate after being immersed in noni fruit juice. An acrylic resin plate of 65 × 10 × 2.5 mm was immersed in 4%, 6%, 8%, 10%, and 12% concentrations of noni fruit juice and distilled water in a control group for 31, 46, and 61 days. The transversal strength of acrylic resin plate was tested using an autograph with a crosshead speed of 1/10mm/second; the distance for the two supporting parts was 50 mm. The data was analyzed by using a One–Way ANOVA test. There was no significant difference in the transversal strength of the plate after being soaked for 31, 46, and 61 days in 4%, 6%, 8%, 10%, and 12% concentrations of the juice. This study showed that the soaking of acrylic resin plate for 31, 46, and 61 days in 4%, 6%, 8%, 10%, and 12% concentrations of noni fruit juice does not decrease the transversal strength.